Answer:two dimensional shapes
Step-by-step explanation:
Answer:
3people/minute
Step-by-step explanation:
75/25=3
Uncle peter-relative
january-month
jesse owens-athlete
william shakespeare-author
sunday-day
chrysler-automobile
The picture is not clear. let me assume
y = (x^4)ln(x^3)
product rule :
d f(x)g(x) = f(x) dg(x) + g(x) df(x)
dy/dx = (x^4)d[ln(x^3)/dx] + d[(x^4)/dx] ln(x^3)
= (x^4)d[ln(x^3)/dx] + 4(x^3) ln(x^3)
look at d[ln(x^3)/dx]
d[ln(x^3)/dx]
= d[ln(x^3)/dx][d(x^3)/d(x^3)]
= d[ln(x^3)/d(x^3)][d(x^3)/dx]
= [1/(x^3)][3x^2] = 3/x
... chain rule (in detail)
end up with
dy/dx = (x^4)[3/x] + 4(x^3) ln(x^3)
= x^3[3 + 4ln(x^3)]
Answer:
i wish i were heather
Step-by-step explanation:
as she ridessss byyyyyy...